2018
DOI: 10.1371/journal.pone.0200997
|View full text |Cite
|
Sign up to set email alerts
|

Can we learn to manage stress? A randomized controlled trial carried out on university students

Abstract: In our research, we examined the efficacy of an Internet-based stress management program. Our interest in evaluating this type of intervention is based on the increasing accessibility of the Internet today, the growth of Internet-based interventions for various psychopathological problems, and the observation that despite the prevalence of stress among university students, only a fraction of students ever seek professional help. Methodology: “I’m managing my stress” (“Je gère mon stresse”), an Internet-based s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(50 citation statements)
references
References 83 publications
1
48
0
1
Order By: Relevance
“…As seen in Multimedia Appendix 2, some studies included more than one type of technology, and thus, the numbers reported in the previous sentence add up to more than the 89 studies included in this review. Although the interventions examined were variable in content and in length, the most common type of intervention examined was internet-based cognitive behavioral therapy (n=28 [42,49,50,57,61,68,72-75,79-81,83-86,88,98,101, 103,107,109,112,113,123,128,129]). The modal length of intervention was 8 weeks.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As seen in Multimedia Appendix 2, some studies included more than one type of technology, and thus, the numbers reported in the previous sentence add up to more than the 89 studies included in this review. Although the interventions examined were variable in content and in length, the most common type of intervention examined was internet-based cognitive behavioral therapy (n=28 [42,49,50,57,61,68,72-75,79-81,83-86,88,98,101, 103,107,109,112,113,123,128,129]). The modal length of intervention was 8 weeks.…”
Section: Resultsmentioning
confidence: 99%
“…The majority of interventions studied offered some level of support or guidance to users—many of these interventions featured coaching from a human (n=33 [41,49-51,58 ,62-66,69,71,73,74,76,79,82-88,94,101,104,105,107,116,122,123,128,129]), whereas others featured automated support (n=18 [44,48, 53,57,59,67,70,77,91,98-101,106,108,112,113,115]), such as prescripted emails. Several studies examined self-guided interventions (n=33 [42,43,45,46,52,54-56,60,61,68,72,75,78, 80,81,89,90,92,93,95,97,102,103,109-111,114,118,119,121,124,125]) in which the participants only had contact with the study staff for research assessments; few studies focused on technology as an adjunct to therapy (n=5 [47,86,100,120,126]), 2 studies provided peer support [96,117], and 1 study had an unclear presence of support (n=1 [127]).…”
Section: Resultsmentioning
confidence: 99%
“…Brinkman 48 suggests some strategies focused on increasing awareness of how to manage anxieties and fears and effectively cope with the COVID-19 virus. Saleh et al 49 showed significant improvements in coping with stress, and greater satisfaction with studies among college students, after applying the online self-help program based on cognitive-behavioral therapy, and composed just of four sessions.…”
Section: Relationship Of Anxiety With Health Life Satisfaction Strementioning
confidence: 99%
“…Orucu and Demir [34] recommended the use of this tool across different cultures and also in the student population. This tool consists of a 14-item scale, but its 10item version is widely used in international studies examining students' perceived stress [35][36][37][38][39]. In general, a higher score indicates a higher perceived stress.…”
Section: Perceived Stressmentioning
confidence: 99%
“…In addition to psychotherapy and treatment, public debate and education about the importance of mental health play a key role in the acceptance of these disorders by society as a whole. Internet-based interventions aimed at reducing stress and mental health problems are also a great opportunity for students who do not seek professional help themselves [38]. Promising interventions may include useful information on websites and social networks, online lectures with experts, online campaigns and challenges focused on good mental health, promotional videos from the perspective of young people.…”
Section: Practical Implications and Interventionsmentioning
confidence: 99%